Environmental sustainability awareness in selected countries - Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2020)
Introduction: The idea of ‘sustainability’ has become increasingly prominent across the globe, applied and discussed at an international, national, and community level. Objective: This paper discussed on the environmental sustainability awareness and elaborates several approaches at four countries; Switzerland, the United States of America, China, and Malaysia. Method: Secondary data are collected with regard to “environmental sustainability” and “awareness” scope matters. Result: The efficiency of implementing environmental sustainability awareness not only increases through responsibility of a single man as well as adoption of technology, but also cooperation between government and community, education and law-making; all work together to protect the environment. Conclusion: The active participation and involvement of citizen is the main key to achieve the environmental sustainability in every country.